Optical Characterization and Lasing in Three-Dimensional Opal-Structures - Nishijima, Yoshiaki; Juodkazis, Saulius (Frontiers in Materials, 2015)
The lasing properties of dye-permeated opal pyramidal structures are compared with the lasing properties of opal films. The opal-structures studied were made by sedimentation of micro-spheres and by sol-gel inversion of the direct-opals. Forced-sedimentation by centrifugation inside wet-etched pyramidal pits on silicon surfaces was used to improve the structural quality of the direct-opal structures. Single crystalline pyramids with the base length of ∼ 100 µm were formed by centrifuged sedimentation. The lasing of dyes in the well-ordered crystalline and poly-crystalline structures showed a distinct multi-modal spectrum. Gain via a distributed feedback was responsible for the lasing since the photonic band gap was negligible in a low refractive index contrast medium; the indices of silica and ethylene glycol are 1.46 and 1.42, respectively. A disordered lasing spectrum was observed from opal films with structural defects and multi-domain regions. The three dimensional structural quality of the structures was assessed by in situ optical diffraction and confocal fluorescence. A correlation between the lasing spectrum and the three-dimensional structural quality was established. Lasing threshold of a sulforhodamine dye in a silica opal was controlled via Förster mechanism by addition of a donor rhodamine 6G dye. The lasing spectrum had a well-ordered modal structure which was spectrally stable at different excitation powers. The sharp lasing threshold characterized by a spontaneous emission coupling ratio β ' 10−2 was obtained.